Alexander Kennedy Isbister (1822-1883) - Kupsch, Walter O. (ARCTIC, 1984)
As a committed and effective spokesman in London, England, for the poor indigenous people of mid-nineteenth-century Rupert's Land - that is how Alexander Kennedy Isbister should be remembered by all Canadians and revered by those who were his people. But he is not. . Church records list Alexander Kennedy Isbister's grandmother on his mother's side as Agatha, an "Indian Women". His grandfather, Alexander Kennedy, hailed from the Orkneys and worked for the Hudson's Bay Company, as did Thomas Isbister, his father. . As was done with many other offspring of the Company's personnel, young Alexander was sent away for his education: first, at ten the Orkneys for a year or so of schooling and then in 1833 to the Red River settlement for more of the same. . For the Company, Isbister travelled through the lower part of the Mackenzie Basin. When he left British North America in 1842, barely 20 years old and never to return, he had acquired some valuable firsthand knowledge of the West and the North. More importantly, he had developed both an intense interest in the geology and geography of the land and a consuming compassion for its people. . Alexander earned his crown by his persistent battle against the injustices he saw being perpetrated by the Company. The battle began when, at age 25, he becamed the trusted representative of petitioners who charged "that the Company impoverished the natives for their own profit". He never came to a halt. In 1871 shareholder A.K. Isbister took up a claim of the Chief Traders and Chief Factors at the General Court of the Hudson's Bay Company. By then he had become the leading authority on all matters affecting British North America. This distinction was not only well earned but also well deserved.